2021
DOI: 10.1007/s40747-021-00398-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance analysis of quantum machine learning with deep learning for diabetes prediction

Abstract: Background Diabetes, the fastest growing health emergency, has created several life-threatening challenges to public health globally. It is a metabolic disorder and triggers many other chronic diseases such as heart attack, diabetic nephropathy, brain strokes, etc. The prime objective of this work is to develop a prognosis tool based on the PIMA Indian Diabetes dataset that will help medical practitioners in reducing the lethality associated with diabetes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 35 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…There is a particular adoption in this frame of reference: in QML models, there are two most important things are state preparation techniques [91], [154] and feature map [88], [89], [95], [146]- [148], different data encoding methods, such as feature extraction methods [81], [95], [99], [141], [150], and data encoding methods, like basis encoding, amplitude encoding [88], [154], and other encodings. The state preparation method is to encode classical data into the quantum state, and the feature map is converted 2D to higher dimensions using Hilbert space [88], [89], [95], [146]- [148].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a particular adoption in this frame of reference: in QML models, there are two most important things are state preparation techniques [91], [154] and feature map [88], [89], [95], [146]- [148], different data encoding methods, such as feature extraction methods [81], [95], [99], [141], [150], and data encoding methods, like basis encoding, amplitude encoding [88], [154], and other encodings. The state preparation method is to encode classical data into the quantum state, and the feature map is converted 2D to higher dimensions using Hilbert space [88], [89], [95], [146]- [148].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the classical system exceeded the quantum system by a little margin. With the PIMA diabetes dataset, H. Gupta et al [95] employed the exploratory data analysis (EDA) and preprocessing technique for data scaling and applied it to the VQC, root mean square propagation (RMSprop), and DL models for classification. They used back-propagation and the VQC approach to assess RMSprop in that research.…”
Section: Medical Healthcare Recordsmentioning
confidence: 99%
“…In the present work, to detect and omit the outliers, quartiles have been employed and it has been mathematically presented as in Eq. ( 1 ) [ 23 ]. where, k symbolizes the presence of the feature vector in m -dimensional feature space ( ).…”
Section: Methodsmentioning
confidence: 99%
“…In this work, most popular ML models such as Logistic Regression (LR), Random Forest (RF), Naive Bayes (NB), Light Grading Boosting Machine (LGBM), and Multilayer feed-forward Perceptron (MLP) have been employed for this purpose. These models have been selected because of their tremendous performance in various tasks [ 23 , 24 ]. Logistic Regression LR has been considered as one of the most simple yet, effective ML models.…”
Section: Methodsmentioning
confidence: 99%
“…Some deep learning approach had been applied into diabetes dataset to get more suitable results for detecting diabetes [ 27 , 34 ]. For example, Gupta et al [ 16 ] used deep learning (DL) and quantum machine learning (QML) to detect diabetes where DL outperformed related QML algorithms.…”
Section: Related Workmentioning
confidence: 99%